ANALISIS KEMAMPUAN PENALARAN MATEMATIS SISWA DITINJAU DARI KEMAMPUAN AWAL - Mohamad Salam; Hasnawati Hasnawati; Ida Ayu Putri Andini; Suhar Suhar; Lambertus Lambertus (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
Mathematical reasoning is a systematic thinking process based on mathematical logic in solving problems that affect the creation of logical decisions based on the knowledge that students already have. This study aims to analyze students' mathematical reasoning abilities based on initial abilities. The method used is qualitative with a descriptive approach using triangulation techniques. The research subjects were class VIIIB students of SMP Negeri 15 Konawe Selatan consisting of 3 students who were selected from 25 students based on their initial abilities. Data collection techniques through written tests and interviews. The results obtained are: (1) students who have high initial abilities meet all indicators of mathematical reasoning, namely making conjectures (P1), doing mathematical manipulation (P2), compiling evidence (P3), making conclusions (P4), and checking the validity of arguments (P5, (2) students who have early abilities are fulfilling some indicators of mathematical reasoning, namely P1, P2, and some P3, and (3) students who have low initial ability meet the P1 and P2 mathematical reasoning indicators. These results indicate that different initial abilities have different mathematical reasoning.